Implementation of an International Information System on Kidney Transplantation - Hennige, M. (Methods of Information in Medicine, 1985)
Kidney transplantations are influenced by a number of factors which are as yet partly unknown or correlate, their mutual dependencies being again unknown. Some of these factors are of a regional or organisational nature. One possibility of gaining new knowledge consists in setting up and analysing an extensive database.With the aid of the information system presented, which is part of a worldwide prospective study on kidney transplantations, it has been possible to build up such a database within a period of three years. It contains information on more than 16,000 kidney transplantations including follow-up data. 212 transplantation centers from all over the world participate in this study. First analyses already showed interesting correlations.
Keywords: Kidney Transplantation; Information System; Data Analysis